INFLUENCE OF TEACHERS’ INSTRUCTIONAL PRACTICES:Collaborative activities in teaching and learning of preschool children in Kiambu West Sub-County; Kenya - Wanjiku, Kang’ara H.; Koech, Peter K. (Machakos University, 2018)
Learning of preschool children has faced numerous challenges which have raised concerns among preschool education stakeholders. Preschool learners have registered and continued to register dismal grades in basic numeracy, language and creativity skills. Thus, the study examined the influence of teachers’ instructional practices on preschool learning in Kiambu West Sub-county, Kiambu County, Kenya. The objective, of the study was to determine the influence of teachers’ instructional practices for collaboration on learning of preschool children in Kiambu West Subcounty; Thestudy wasbased on instructional, learning andskills acquisition theories. The study adopted mixed methods approach, concurrent triangulation design. Target population comprised of 80 head teachers, 187 preschool teachers and 240 parents’ representatives and 2400 preschool learners all totaling to 2907. Using the Central Limit Theorem, a sample of 10 preschools and 326 respondents were selected. Stratified sampling was applied to create five strata based on number of zones. From each zone, two head teachers and 11 preschool teachers were selected using purposive sampling. 4 parents’ representatives and 48 preschool learnerswere selected using simple random sampling. Questionnaires were used to collect data from preschool teachers, interview schedules were used to collect data from head teachers, whereas focus group discussion was used to collect data fromparents’ representatives and observation checklists were used for collection of data from preschool learners.Qualitative data was analyzed thematically along the objectives and presented in narrative form whereas quantitative data was analyzed descriptively and inferentially using statistical package for social science (SPSS 23) and presented using statistical tables. The study established that preschool teacherswho are prepared for collaboration with other education stakeholders enhance learning in preschools. The study established that preschool teachers do not plan lessons together with colleagues which do not enable them to promote preschool learners’ language skills, numeracy skills and learners’ acquisition of creativity skills.
Keywords: Preschool Learners